SPECIFIC FEATURES OF CONTENT BASED LEARNING FOR ESP IN HIGHER EDUCATION (IN THE FIELD OF BIOLOGY) (Archive of Conferences, 2022)
In this article The most important difference lies in the learners and their purposes for learning English. ESP students are usually adults who already have some acquaintance with English and are learning the language in order to communicate a set of professional skills and to perform particular job-related functions. An ESP program is therefore built on an assessment of purposes and needs and the functions for which English is required.